Pengaruh Profitabilitas terhadap Nilai Perusahaan dengan Kebijakan Deviden sebagai Variabel Intervening - Dwi Atmikasari; Iin Indarti; Elma Muncar Aditya (STIE Widya Manggala, 2020)
This study aimed to determine the effect of profitability on firm value through dividend policy as the intervening variable. The population and sample used were 37 companies listed in Indonesia stock exchange for 3 years (2015-2017). The sampling technique used was non-random sample using non-probability technique with a method based on saturated sampling. The analytical tool used was path analysis test which waspreviously tested by descriptive test, classical assumption test and hypothesis test. The results of the study indicated that profitability (X) had a positive and significant effect on firm value (Y). Profitability (X) had a positive and significant effect on dividend policy (Z). Dividend policy (Z) had a positive and significant effect on firm value (Y). Profitability (X) had a positive and significant effect on firm value (Y) through dividend policy (Z) as the intervening variable. The result of determination coefficient (R2) is 0,500%. It means the influence of profitability and dividend policy on firm value as much as 50%. While the remaining 50% is influenced by other variables outside the variables studied.